2017
DOI: 10.1016/j.pmedr.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal trajectory of post-surgical % total weight loss among middle-aged women who had undergone bariatric surgery

Abstract: Middle-aged women are at a higher risk of being obese. We examined the trajectory of post-surgical % total weight loss (%TWL) among middle-aged female bariatric patients. We fitted sequential generalized estimating equations models to analyze a sample of women who received bariatric surgery in 1995–2012, aged 40–65 years at the time of surgery (N = 158,292) whose pre-operative body mass index (BMI) was ≥ 30 kg/m2 in the Bariatric Outcomes Longitudinal Database. The %TWL computed by 100% × (pre-surgery BMI − po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
4
16
0
Order By: Relevance
“…Multiple guidelines have described several predictors of successful post-operative weight loss such as behavioral changes, pre-operative weight loss and nutrition therapy (12). Similar to other cohorts we described the tendency to increase on %TWL and %EWL in the rst year and a plateau after that time (13,14). In this study we found that baseline BMI, weight loss before surgery, nutritional follow-up and time of physical activity during the 12 months after surgery were associated with a signi cant change in %TWL and %EWL and we quanti ed the size of the impact.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Multiple guidelines have described several predictors of successful post-operative weight loss such as behavioral changes, pre-operative weight loss and nutrition therapy (12). Similar to other cohorts we described the tendency to increase on %TWL and %EWL in the rst year and a plateau after that time (13,14). In this study we found that baseline BMI, weight loss before surgery, nutritional follow-up and time of physical activity during the 12 months after surgery were associated with a signi cant change in %TWL and %EWL and we quanti ed the size of the impact.…”
Section: Discussionsupporting
confidence: 86%
“…Pre-operative BMI has an important effect on weight loss outcomes among patients who had bariatric surgery (13,14). Seo et al described the increase in %TWL was higher among patients treated with RYGB whose pre-operative BMI was ≥40 and it kept increasing even up to 5 years after surgery (13). Contrarily, we found that in the subgroup of patients with greater weight and BMI before surgery, the weight loss was lower at the end of follow-up, a nding that has been described in other publications (12,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BDI-II scores), standardized pre and post-operative management and uniform surgical technique performed by a single surgeon. An inclusion criterion of at least 12 months after surgery was employed as it is shown that weight loss trajectory increases sharply in the first few months after BS, then plateaus or decreases at approximately 12 months [30].…”
Section: Discussionmentioning
confidence: 99%
“…The main inducement of obesity is not only excess food intake but also low physical activity (Xing et al , 2017). A variety of methods are used to lose weight including diet, exercise, drugs and surgical operation (Seo et al , 2017). Considering the surgical risk and the side effects caused by the drugs, most people tend to achieve and maintain a healthy weight by diet and exercise.…”
Section: Introductionmentioning
confidence: 99%